2007
DOI: 10.1677/jme.1.00010
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid-related orphan receptor   regulates several genes that control metabolism in skeletal muscle cells: links to modulation of reactive oxygen species production

Abstract: Retinoid-related orphan receptor g (RORg) is an orphan nuclear hormone receptor (NR) that is preferentially expressed in skeletal muscle and several other tissues, including pancreas, thymus, prostate, liver and testis. Surprisingly, the specific role of RORg in skeletal muscle, a peripheral tissue, has not been examined. Muscle is one of the most energy demanding tissues which accounts for w40% of the total body mass and energy expenditure, O75% of glucose disposal and relies heavily on b-oxidation of fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…The specific functions of this protein are not fully understood. However, a study in mouse skeletal muscle cells suggested that RORC increased the expression of the retinoid-related orphan receptor alpha RORα gene, and thereby modulated the expression of genes involved in the control of lipid homeostasis, such as fatty acid binding protein, fatty acid translocase, lipoprotein lipase, and uncoupling protein 3 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The specific functions of this protein are not fully understood. However, a study in mouse skeletal muscle cells suggested that RORC increased the expression of the retinoid-related orphan receptor alpha RORα gene, and thereby modulated the expression of genes involved in the control of lipid homeostasis, such as fatty acid binding protein, fatty acid translocase, lipoprotein lipase, and uncoupling protein 3 21 .…”
Section: Discussionmentioning
confidence: 99%
“…GLUT5 is expressed in skeletal muscle of human (14,40,41,66,71,81,125,137,143,144), rat (40), and mouse (131). In fact, GLUT5 is, along with GLUT4 and GLUT12, one of the more significantly expressed GLUTs in human skeletal muscle compared with the other members of the GLUT family (144).…”
Section: Physiology and Functionmentioning
confidence: 99%
“…In fish a weak expression of this gene in cardiac muscle and somites has been reported in zebrafish larvae, as well as in the brain [8]. The role of ROR-g in these organs is still unclear, but it has been suggested that it is involved in the regulation of muscle metabolism and growth control [37]. When analysing the expression of ROR-g in trout cell lines and primary cultures, it was found that this gene was highly expressed in the fibroblast-like cell lines.…”
Section: Relative Expressionmentioning
confidence: 99%